2011
DOI: 10.1158/1541-7786.mcr-11-0327
|View full text |Cite|
|
Sign up to set email alerts
|

αB-Crystallin, an Effector of Unfolded Protein Response, Confers Anti-VEGF Resistance to Breast Cancer via Maintenance of Intracrine VEGF in Endothelial Cells

Abstract: Effective inhibition of angiogenesis targeting the tumor endothelial cells requires identification of key cellular and molecular mechanisms associated with survival of vasculatures within the tumor microenvironment. Intracellular autocrine (intracrine) VEGF production by endothelial cells plays a critical role on the vasculature homeostasis. In vitro breast cancer cell-stimulated activation of the unfolded protein response (UPR) of the endothelial cells contributes to maintenance of the intracrine VEGF levels … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 40 publications
3
71
0
Order By: Relevance
“…In human endometrium, Cryab expression is upregulated during the window of implantation (Gruidl et al 1997), which further supported a role for Cryab in implantation. Additional studies have found that Cryab could regulate angiogenesis by modulating the expression of vascular endothelial growth factor (VEGF), which was the main factor responsible for increased endometrial vascular permeability at implantation (Rabbani & Rogers 2001, Rockwell et al 2002, Kase et al 2010, Ruan et al 2011. Inhibition of VEGF could significantly reduce the number of implantation sites (Rabbani & Rogers 2001, Rockwell et al 2002, Guo et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…In human endometrium, Cryab expression is upregulated during the window of implantation (Gruidl et al 1997), which further supported a role for Cryab in implantation. Additional studies have found that Cryab could regulate angiogenesis by modulating the expression of vascular endothelial growth factor (VEGF), which was the main factor responsible for increased endometrial vascular permeability at implantation (Rabbani & Rogers 2001, Rockwell et al 2002, Kase et al 2010, Ruan et al 2011. Inhibition of VEGF could significantly reduce the number of implantation sites (Rabbani & Rogers 2001, Rockwell et al 2002, Guo et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…33,39 Upregulation of CryaB in ECs was shown to confer anti-VEGF resistance in cancer cells, suggesting that CryaB inhibition may function in addition to anti-VEGF in therapies. 40 Regulation of CryaB by miR-126-3p suggests that miR-126-3p may have therapeutic implications in other CryaB-related diseases than AMD, including cancer and neurodegenerative diseases. Although RPE cells from CryaB −/− mice shown increased death under oxidative stress, CryaB downregulation by miR-126-3p did not cause RPE cell death (Supplementary Figure S7), suggesting the safety of targeting CryaB using miR-126-3p mimic.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Additional genes of interest such as RAD51, EGFR, ERBB2, and CRYAB were also included [35,[39][40][41][42]. The complete gene list can be found in Supplementary Table 1.…”
Section: Gene Expression Profiles Gene Selection and Probe Designmentioning
confidence: 99%